1995
DOI: 10.1080/03014469500004122
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric comparison between high- and low-altitude Saudi Arabians

Abstract: Measurements of weight, height, mid-upper arm circumference, mid-upper arm muscle circumference and skinfold thickness over the triceps region were made in 437 high-altitude residents (3150m above sea level) aged 16-60 years and 468 low-altitude residents (500 m above sea level) aged 16-60 years in southern Saudi Arabia. Compared with low-altitude residents, high-altitude residents were found to be significantly heavier and taller, but to have nearly similar mid-upper arm circumference, mid-upper arm muscle ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
3
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
2
3
1
Order By: Relevance
“…Several studies have investigated fat patterning variation in Asian herders (Beall and Goldstein, 1992;Leonard et al, 1996) or in mountain populations (Hannon et al, 1969;Frisancho and Baker, 1970;Bharadway, 1972;Bhardway et al, 1973Bhardway et al, , 1984Beall et al, 1977;Miklashevskaya et al, 1977Miklashevskaya et al, , 1979Khalid, 1995;Obert et al, 1994). The results are not fully comparable with the present data, because of the higher altitude of the populations examined and a lack of a detailed analysis of adiposity.…”
Section: Discussioncontrasting
confidence: 67%
“…Several studies have investigated fat patterning variation in Asian herders (Beall and Goldstein, 1992;Leonard et al, 1996) or in mountain populations (Hannon et al, 1969;Frisancho and Baker, 1970;Bharadway, 1972;Bhardway et al, 1973Bhardway et al, , 1984Beall et al, 1977;Miklashevskaya et al, 1977Miklashevskaya et al, , 1979Khalid, 1995;Obert et al, 1994). The results are not fully comparable with the present data, because of the higher altitude of the populations examined and a lack of a detailed analysis of adiposity.…”
Section: Discussioncontrasting
confidence: 67%
“…Several studies have investigated fat patterning variation in Asian herders (Beall and Goldstein, 1992;Leonard et al, 1996) or in mountain populations (Hannon et al, 1969;Frisancho and Baker, 1970;Bharadway, 1972;Bhardway et al, 1973Bhardway et al, , 1984Beall et al, 1977;Miklashevskaya et al, 1977Miklashevskaya et al, , 1979Khalid, 1995;Obert et al, 1994). The results are not fully comparable with the present data, because of the higher altitude of the populations examined and a lack of a detailed analysis of adiposity.…”
Section: Discussioncontrasting
confidence: 67%
“…A large number of studies have been conducted on various aspects of 'man versus altitude' (Khalid, 1995;Beall et al, 1997;Weitz et al, 2004;Kapoor and Kapoor, 2005); however, only a few studies have focused on the effects of both altitude and ageing on human morphology, physiology, and nutritional status (Tyagi and Kapoor, 1999;Kaur and Kapoor, 2003) and none of these studied primitive tribal populations. Kapoor and Kapoor (1987) found that hematological traits, including hemoglobin level, red blood cell count, white blood cell count, and mean corpuscular hemoglobin, increased with an increase in altitude.…”
Section: Introductionmentioning
confidence: 99%